Persepsi Siswa Terhadap Sampah Organik Maupun Sampah Anorganik - Lamtiar Ferawaty Siregar; Dewi Natalia Marpaung; Jesi Jecsen Pongkendek; Novike Bela Sumanik (Faculty of Teacher Training and Education, Musamus University, 2020)
Environmental pollution due to inappropriate waste management is a global problem. Open dumping and burning of waste in the open are the main waste management practices often applied to low-income countries. The biggest environmental problem in Indonesia is usually garbage. Generally, the waste that is often found in the school environment is organic and inorganic. Plastics, drink bottles and paper are examples of the types of inorganic waste often found in the school environment. This study aims to determine students' perceptions of organic and inorganic waste grouping as well as waste management and utilization. The data collection technique is to use a closed questionnaire. A total of 15 items and a total sample of 29 people. The data obtained from the questionnaire results are then made in narrative form. Based on the results of the research, some students have not been able to distinguish between organic and inorganic waste. The lack of available trash bins in the school environment can trigger students to care less about disposing of garbage in its place, some students do not also know waste management and utilization.